A Christmas without snow [videorecording (DVD)] - Korty, John; Houseman, John. 1902-1988; Learned, Michael (Echo Bridge Home Entertainment, 2004)
A recently divorced woman moves to San Francisco to start a new life. She joins a church choir and meets new friends and learns special life lessons.